Serum resistin: a biomarker of breast cancer in postmenopausal women? Association with clinicopathological characteristics, tumor markers, inflammatory and metabolic parameters. - Dalamaga, Maria; Sotiropoulos, George; Karmaniolas, Konstantinos; Pelekanos, Nicolaos; Papadavid, Evangelia; Lekka, Antigoni (Clin Biochem, 2013)
OBJECTIVE: Previous few studies have shown that resistin is significantly elevated in breast cancer (BC) patients. Therefore, we investigated whether serum resistin could be used as a potential diagnostic and prognostic tool for postmenopausal BC (PBC), taking into account clinicopathological features, serum tumor markers, anthropometric, metabolic, and, for the first time, inflammatory parameters. METHODS: Serum resistin, tumor markers (CA 15-3 and CEA), metabolic, anthropometric and inflammatory parameters (TNF-α, IL-6, hsCRP) were determined in 103 postmenopausal women with incident, pathologically confirmed, invasive BC, 103 controls matched on age and time of diagnosis, and 51 patients with benign breast lesions (BBL). RESULTS: Mean serum resistin was significantly higher in cases than in controls and patients with BBL (p<0.001). In patients, resistin was significantly associated with tumor and inflammatory markers, cancer stage, tumor size, grade and lymph node invasion but not with anthropometric, metabolic parameters and hormone receptor status. Multivariable regression analysis revealed that serum IL-6 (p=0.02) and cancer stage (p=0.048) were the strongest determinants of serum resistin in cases adjusting for demographic, metabolic and clinicopathological features. Although resistin's diagnostic performance was low based on ROC curve analysis [0.72, 95% CI: 0.64-0.79], it could, however, represent a BC biomarker reflecting advanced disease stage and inflammatory state. CONCLUSION: Further prospective and longitudinal studies are needed to evaluate whether serum resistin could be used as a prognostic tool in BC monitoring and management. More research is essential to elucidate resistin's ontological role in the association between obesity, representing a chronic low-grade subclinical inflammation, and PBC.
Keywords: Aged; Biomarkers, Tumor; Breast Neoplasms; C-Reactive Protein; Female; Humans; Interleukin-6; Middle Aged; Obesity; POSTMENOPAUSE; Resistin; Tumor Necrosis Factor-alpha